Thermal analysis of melting effect on Carreau fluid flow around a stretchable cylinder with quadratic radiation - Lim Yeou Jiann; Ahmad Qushairi Mohamad; Noraihan Afiqah Rawi; Dennis Ling Chaun Ching; Nor Athirah Mohd Zin; Sharidan Shafie (Propulsion and Power Research, 2024)
The melting phenomenon plays a critical role in optimizing the performance of power storage, electronic cooling, and semiconductor devices. The present study aims to analyze the melting effect on the flow of Carreau fluid over a stretchable cylinder, with special consideration given to the impact of quadratic thermal radiation. Similarity variables and the homotopy analysis method are used to simplify and determine the semi-analytical homotopic solutions of the governing equations. The present findings reveal that the melting parameter increases the heat transfer rate by more than 10% for both fluids, water (Pr = 0.71), and polymer (Pr = 10). However, as the temperature ratio due to quadratic radiation increases, the local Nusselt number for water has been reduced by 25%, and an even more substantial reduction is observed for the polymer. The present study offers valuable insights into achieving optimal efficiency in electronic devices.